Causes of the male-female ratio of depression based on the psychosocial factors - Tang, Jun; Zhang, Tianyi (Frontiers in Psychology, 2022)
Recently, depression has been a great concern of researchers, and the research on male-female ratio of depression mainly covers the fields of epidemiology and clinical studies. This study is made to explore the causes of the male-female ratio of depression from a humanistic perspective, namely, the psychosocial factors, and thus providing some support and reference for further research on depression. Thereby, the authors select and analyze words lists closely collocated with “depression” according to word score and frequency through the word sketch in enTenTen20 by the corpus tool “Sketch Engine”. Meanwhile, the above words are be further explored for the causes of male-female ratio in depression from the biological, psychological and social aspects based on the Biopsychosocial Model as well as some existing relevant medical research findings. Consequently, women are found to be more likely to suffer from emotional problems and depression than men under the influence of biological basis, general psychological characteristics and social environment interference.